Degradation of halogenated aliphatic compounds by Xanthobacter autotrophicus GJ10. - Janssen, D B (1985)
A bacterium that is able to utilize a number of halogenated short-chain hydrocarbons and halogenated carboxylic acids as sole carbon source for growth was identified as a strain of Xanthobacter autotrophicus. The organism constitutively produces two different dehalogenases. One enzyme is specific for halogenated alkanes, whereas the other, which is more heat stable and has a higher pH optimum, is specific for halogenated carboxylic acids. Haloalkanes were hydrolyzed in cell extracts to produce alcohols and halide ions, and a route for the metabolism of 1,2-dichlorethane is proposed. Both dehalogenases show a broad substrate specificity, allowing the degradation of bromine- and chlorine-substituted organic compounds. The results show that X. autotrophicus may play a role in the degradation of organochlorine compounds and that hydrolytic dehalogenases may be involved in the microbial metabolism of short-chain halogenated hydrocarbons in microorganisms.